Estimativa Da Água No Solo Em Floresta de Eucalyptus Grandis - Rodrigues, Valdemir Antonio [UNESP]; Fenner, Paulo Torres [UNESP]; Sansigolo, Cláudio Angeli [UNESP]; Moraes, Maria Helena [UNESP] (My University, 2012)
The study aimed to assess the moisture and density of the soil, the amount of water stored in the profile, and the average soil's porosity with Eucalyptus grandis reforestation, compared to bare soil. The study areas are located in the Paulista region, in São Paulo, Brazil. The samples were collected in layers of 0, 20, 40, 60, 100 and 300 cm, in the months of April, June, August and October 2008. The results show that the density is lower and the porosity is higher in Eucalyptus forest soil compared to bare soil, due to the higher content of organic matter in forest leaf litter. Furthermore, the forest soil has a lower amount of water stored in profile than the bare soil without vegetation.

O trabalho teve por objetivo avaliar a umidade e densidade do solo, a quantidade de água armazenada no perfil e a porosidade média do solo com reflorestamento de Eucalyptus grandis, em comparação com o solo descoberto. As áreas de estudo estão localizadas no município de Lençóis Paulista, São Paulo, Brasil. As amostras foram coletadas nas camadas de 0; 20; 40; 60; 100 e 300 cm, nos meses de abril, junho, agosto e outubro de 2008. Os resultados evidenciam que a densidade é menor e a porosidade é maior no solo sob floresta de Eucalyptus quando comparado com o solo descoberto, em decorrência do maior teor de matéria orgânica na serrapilheira florestal. Além disso, o solo florestal apresenta menor quantidade de água armazenada no perfil do que o solo descoberto sem vegetação.
Soil water estimation in eucalyptus grandis forest
Keywords: Eucalyptus; Soil; Storage; Water; angiosperm; density; estimation method; forest soil; leaf litter; porosity; reforestation; soil moisture; soil organic matter; soil water; soil-vegetation interaction; Eucalyptus grandis